Rac1 Polymorphisms and Thiopurine Efficacy in Children With Inflammatory Bowel Disease. Issue 4 (October 2015) - Lev-Tzion, Raffi; Renbaum, Paul; Beeri, Rachel; Ledder, Oren; Mevorach, Raphael; Karban, Amir; Koifman, Eduard; Efrati, Edna; Muise, Aleixo M.; Chowers, Yehuda; Turner, Dan
Abstract: Objectives: Thiopurines are effective for maintenance of remission in inflammatory bowel disease (IBD) in only about half of patients. Predictors of response may assist in selecting the most appropriate patients for thiopurine therapy. Thiopurines inhibit Rac1, a GTPase that exerts an antiapoptotic effect on T-lymphocytes. A genetic association was recently demonstrated between a Rac1 single nucleotide polymorphism (SNP) and poorer response to thiopurines in adult patients with Crohn disease. We aimed to determine whether Rac1 SNPs are associated with response to thiopurines in children with IBD. Methods: Children with IBD treated with thiopurines were prospectively followed for 1 year and were genotyped for 3 Rac1 SNPs previously found to be relevant to IBD: rs10951982, rs4720672, and rs34932801. The rate of sustained steroid-free remission (SSFR) without treatment escalation by 12 months was compared between wild types (WTs) and heterozygotes. Results: A total of 59 patients were studied (63% boys, 80% having Crohn disease, mean age 13 ± 4.1). Nineteen of the 41 WT (46%) and 9 of the 15 (60%) heterozygotes for rs10951982 were in SSFR ( P  = 0.55). Similarly, 21 of the 45 (47%) WT and 8 of the 12 (67%) heterozygotes for rs4720672 were in remission ( P  = 0.33). Finally, 21 of the 45 (47%) WT and 3 of the 5 (60%) heterozygotes for rs34932801 were in remission ( P  = 0.66). All of the 3 comparisons remained nonsignificant in a sensitivity analysis of only the patients with Crohn disease. Conclusions: We did not find an association between 3 Rac1 SNPs and thiopurine effectiveness by 12 months in a prospective study of children with IBD. Other predictors of response should be sought to optimize patient selection for thiopurine therapy.